Pembinaan Spiritualitas Jemaat dalam Upaya Meningkatkan Kesetiaan Beribadah di GKSI Jemaat Kristus Jambuh Balai - Dedi Dedi (BADAN PENERBIT STIEPARI PRESS, 2025)
This Community Service Program (PkM) aims to foster congregational spirituality to enhance worship commitment at GKSI Jemaat Kristus Jambuh Balai. The background of the activity arises from the declining participation in worship, where worship is often perceived merely as a routine. The implementation method applied a participatory approach through biblical teaching, communal prayer, and reflective discussions involving active congregation engagement. The results indicate a paradigm shift: worship is now understood as a spiritual encounter deepening the relationship with God rather than a mere obligation. Congregational motivation also increased, demonstrated by more consistent attendance and greater openness to service. The evaluation revealed challenges in time allocation and program continuity; however, overall, the spiritual formation proved effective. This program recommends the continuity of spiritual formation as a structured church agenda, involving families and leaders as models of faith to sustain worship commitment.